Model Arisan Sembako: Tinjauan Fiqh dan Ekonomi (Studi Kasus di Desa Seko Besar, Sarolangon Jambi) - Muhammad Idris; Ambok Pangiuk; Ahsan Putra Hafiz (Indonesian Journal of Islamic Economics and Business, 2020)
This paper aims to discuss the analysis of the economic value of the basic food arisan system for wedding costs in Seko Besar Village, Pauh District, Sarolangun Jambi Regency. The data techniques in this study used observation, interview and documentation techniques, while for data analysis the researchers used descriptive qualitative analysis. The results of the research are as follows: the implementation of basic food arisan for wedding expenses is done to reduce the economic needs of the community and is carried out according to the needs of the members who will hold a wedding party. The basic food arisan is carried out in consultation with the members and carried out in a family manner, in order to meet the needs of the wedding costs. The impact of basic food arisan can ease the burden on the economic needs of arisan members and strengthen family relationships because of the elements of mutual help and friendship. Analysis of the economic value of the basic food arisan system for wedding expenses that has absolutely no elements of usury, gambling, fraud, extortion, or chance and has met the criteria that allow arisan in Islamic economics